Screening for Anemia Through Hemoglobin (Hb) Tests in Female Students at STIKes Muhammadiyah Ciamis - Euis Tia Istianah; Rivana Ariyadi; Crystia Dwimulyani (Mukhtabar Journal of Medical Laboratory Technology, 2025)
Background & Objectives: Indonesia ranked 5th in the world (22.331%) in terms of anemia incidence in 2019, after Pakistan (22.409%), Nigeria (25.475%), China (54.041%), and India (187.325%). The prevalence of anemia in Indonesia based on data from the 2018 Basic Health Research was 48.9%. Globally, the prevalence of anemia is higher in adolescent girls than in adolescent boys. Anemia is a disease caused by a lack of red blood cells. This study aims to determine anemia screening through hemoglobin testing in female students at STIKes Muhammadiyah Ciamis. Method: The method used in this study was descriptive, with the respondents being female students at STIKes Muhammadiyah Ciamis. Hemoglobin levels were measured using a spectrophotometer with the synehemoglobin method. This study was conducted at the Hematology Laboratory of STIKes Muhammadiyah Ciamis in May 2024. Results: Based on the examination results of 42 samples, 1 person (2%) was found to have moderate anemia, 4 people (10%) had mild anemia, and 37 people (88%) had normal results. Conclusion: The average hemoglobin level of female students at STIKes Muhammadiyah Ciamis is normal.